Animal and Human Brucellosis in Pakistan - Jamil, Tariq; Khan, Aman Ullah; Saqib, Muhammad; Hussain, Muhammad Hammad; Melzer, Falk; Rehman, Abdul; Shabbir, Muhammad Zubair; Khan, Mumtaz Ali; Ali, Shahzad; Shahzad, Asim; Khan, Iahtasham; Iqbal, Mudassar; et al. (Frontiers in Public Health, 2021)
Brucellosis is a bacterial zoonotic disease that affects many animal species and can be transmitted to humans via direct contact or via contaminated food. Although brucellosis is a serious health hazard, its public health concern has been neglected in many countries. In some developing countries, such as Pakistan, where brucellosis is endemic, this disease continues to be of importance. A literature search for the past 11 years (2011–2021) provided a comprehensive insight into brucellosis in Pakistan. In this review, particular emphasis was placed on occurrence, diagnostic tests used, and prevention, treatment, and control in the context of the “One Health” approach.